Analisis Kinerja Bank Syariah Dengan Menggunakan Maqashid Syariah Index - Yuniar Agit Hastuti; Safira Safira (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2019)
This study aims to examine the development of Islamic banking performance and see the suitability of Islamic banking performance with maqashid sharia by using the Maqashid Syariah Index. This research was conducted at Sharia Commercial Banks registered at Bank Indonesia (BI) and Financial Services Authorization (OJK). Samples were taken using purposive sampling method. The total sample in this study was 11 companies during 2013-2017. Then Islamic banks are measured and in their performance ranking based on 3 steps: 1) performance ratio 2) performance indicators 3) maqashid syariah index as a whole. Based on the results of the study, it shows that Islamic maybank and Bank BCA have the best development among other banks, in 2013-2017 the Maybank Sharia has the highest performance with a value of 36.76%. And the lowest performance occurs in Bank Syariah Bukopin with a value of 16.53%.